2017
DOI: 10.1016/j.humov.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The action-specific effect of execution on imagination of reciprocal aiming movements

Abstract: Past research has shown that the movement times of imagined aiming movements were more similar to actual movement times after the individual has experienced executing the movements. The purpose of the present study was to determine if experience with a set of movements altered the imagination of movements that were not experienced. Participants imagined a series of reciprocal aiming movements in different movement difficulty contexts (created by altering target width and movement amplitude) before and after ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…That is, the base movement times (as indicated by the intercept from the Fitts’ Law equation) tend to be greater for imagined compared to executed movements when the task difficulty is altered and time is no longer constrained (e.g., Wong et al 2013 ). This trend has been primarily attributed to the additional demands placed on the control of imagined movements, including the need to index the start and end of the movements (e.g., lifting the stylus before returning to a similar position) (Glover and Baran 2017 ; Glover and Dixon 2013 ; for an alternative explanation, see Yoxon et al 2015 , 2017 ). In the context of the present study, it is possible that the additional demands that are placed on the control of imagined movements could no longer be accommodated within the movement time, because it was constrained, and thus alternatively manifested in a larger estimate of spatial error.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, the base movement times (as indicated by the intercept from the Fitts’ Law equation) tend to be greater for imagined compared to executed movements when the task difficulty is altered and time is no longer constrained (e.g., Wong et al 2013 ). This trend has been primarily attributed to the additional demands placed on the control of imagined movements, including the need to index the start and end of the movements (e.g., lifting the stylus before returning to a similar position) (Glover and Baran 2017 ; Glover and Dixon 2013 ; for an alternative explanation, see Yoxon et al 2015 , 2017 ). In the context of the present study, it is possible that the additional demands that are placed on the control of imagined movements could no longer be accommodated within the movement time, because it was constrained, and thus alternatively manifested in a larger estimate of spatial error.…”
Section: Discussionmentioning
confidence: 99%
“…As well as being familiarised with the aiming task, it was essential for participants to be initially familiarised with the criterion times prior to formally undertaking the execution and imagery protocols. Likewise, the equivalence between execution and imagery is often contingent upon the prior practice or physical exposure to the task dynamics, where a representation may be initially constructed in practice and later awakened in imagery (Yoxon et al 2015 , 2017 ). Thus, participants undertook one set of practice trials when they were first introduced to each of the criterion times.…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence has suggested that additional physical practice of the movement can reduce the imagined times, and subsequently bring them closer to the executed times (Wong et al, 2013;Yoxon et al, 2015;Yoxon et al, 2017). This experience-dependent effect of imagined movements has been attributed to the development and enhancement of the codes responsible for matching imagined, perceived and executed actions, which can be built upon by sensorimotor training or exposure to the unique task environment.…”
Section: Modulation Effectsmentioning
confidence: 99%
“…Decety & Jeannerod, 1995;Papaxanthis, Pozzo, Skoura, & Schieppati, 2002;Sirigu et al, 1995;Sirigu et al, 1996;Slifkin, 2008;Wong, Manson, Tremblay, & Welsh, 2013;Yoxon, Pacione, Song, & Welsh, 2017;Yoxon, Tremblay, & Welsh, 2015). The relation between ID and MT is referred to as Fitts' Law (Fitts, 1954;Fitts & Peterson, 1964), and can be more precisely calculated using the following formula: MT = a + b (ID), where a and b are empirically derived constants pertaining to the base MT and the slope of the relation between MT and ID, respectively.…”
mentioning
confidence: 99%
“…Research investigating the representation of mental imagery has revealed neural and functional bases of action representation, perception, and production, that are broadly consistent with physical performance (Macuga & Frey, 2012; Moulton & Kosslyn, 2009; Vogt et al, 2013). For example, behavioural, mental chronometry research, where imagers either self-time or respond to the events imagined, has identified the preservation of cognitive, motor, and biomechanical constraints that influence physical performance during imagery (e.g., Bakker et al, 2007; Dahm & Rieger, 2016; Decety & Jeannerod, 1996; Papaxanthis et al, 2002; Sirigu et al, 1995; Yoxon et al, 2017). In addition, imagery and overt action planning tend to activate a broad network of frontal, parietal, and subcortical neural regions (Hetu et al, 2013; Jeannerod, 2001), where the accuracy of the image promotes the partial reactivation of perceptual, motor, and introspective states that are underlined by past sensorimotor experience (Barsalou, 1999, 2008).…”
Section: Introductionmentioning
confidence: 99%